Decoding telomere protein Rap1: Its telomeric and nontelomeric functions and potential implications in diabetic cardiomyopathy. Issue 19 (2nd October 2017) - Cai, Yin; Kandula, Vidya; Kosuru, Ramoji; Ye, Xiaodong; Irwin, Michael G.; Xia, Zhengyuan
ABSTRACT: Mammalian Rap1, the most conserved telomere-interacting protein, beyond its role within nucleus for the maintenance of telomeric functions, is also well known for its pleiotropic functions in various physiological and pathological conditions associated with metabolism, inflammation and oxidative stress. For all these, nowadays Rap1 is the subject of critical investigations aimed to unveil its molecular signaling pathways and to scrutinize the applicability of its modulation as a promising therapeutic strategy with clinical relevance. However, the underlying intimate mechanisms of Rap1 are not extensively studied, but any modulation of this protein level has been associated with pathologies like inflammation, oxidative stress and deregulated metabolism. This is considerably important in light of the recent discovery of Rap1 modulation in diseases like cancer and cardiac metabolic disorders. In this review, we focus on both the telomeric and nontelomeric functions of Rap1 and its modulation in various health risks, especially on the heart.